Mechanistic insights into green diesel production via CuNi LDH@Al isopropoxide-catalyzed palm oil deoxygenation: a study using in-situ XAS and DFT - Ibrahim, Naeemah A.; Abdull-Aali Jwaid, Thaer; Obeas, Laith K.; Abdulkareem-Alsultan, G.; Asikin-Mijan, N.; Samidin, Salma; Asma-Samsudin, N.; Fawzi Nassar, Maadh; Lee, H. V.; Taufiq-Yap, Yun Hin; Vo, Dai Viet N.; Silas, Kiman (Elsevier, 2026)
The catalysts that were prepared by combining Cu and Ni into the LDH structure had a higher concentration of both Cu and Ni than the catalysts with lower concentrations of Cu and Ni. Because they have more available surface area, this increases the amount of surface area available for chemical reactions. In addition, based on the catalyst's density of acid and base sites (both of which are important for the deoxygenation of oils), Cu(1%)Ni(6%)LDH@Al was determined to be the most effective catalyst. It has a very large density of acid sites (3.701 mmol/g) and a relatively small density of base sites (0.332 mmol/g). As such, it was able to achieve a hydrocarbon yield of 77.72 %, and an n-C17 yield of 92.55 %. In addition, the authors demonstrated through in-situ XAS measurements made during the course of a reaction, that there were significant changes to the coordination geometry of both Cu and Ni. Specifically, the authors found that the presence of Cu increased the structural integrity of the Ni-containing component of the catalyst. Additionally, DFT studies were conducted to evaluate the likelihood of the simultaneous occurrence of hydrogenation/dehydrogenation processes occurring on the catalyst surface. Through these studies, the authors found that hydroxyl groups on the catalyst surface, generated by the reduction of nickel, facilitate the formation of oxygen vacancies and promote the occurrence of both decarboxylation (DCO2) and decarbonylation (DCO) pathways. The ability of the Ni-Cu hetero-structure to undergo simultaneous hydrogenation/dehydrogenation processes indicates its potential for the creation of green diesel without the need for an external hydrogen source.